Vitamin B12 and diabetic neuropathies - V.A. Serhiyenko; M.-Y. Markevych; V.B. Sehin; A.A. Serhiyenko (Mìžnarodnij Endokrinologìčnij Žurnal)
Vitamin B12 (cyanocobalamin, cobalamin) is an essential cofactor in two important biochemical pathways: methylmalonic acid metabolism and methionine synthesis from homocysteine. In addition to hematologic abnormalities (megaloblastic anemia or even pancytopenia), cobalamin deficiency can cause neurologic symptoms similar to diabetic neuropathy (DN). The underlying molecular mechanisms of DN are still unclear. Most studies have identified the contribution of low-grade chronic inflammation (LGCI) and oxidative stress (OS) to the development of DN. Immunohistochemical studies of calf muscle nerve biopsies obtained from patients with diabetes mellitus and DN indicate activation of the LGCI pathway caused by increased levels of advanced glycation end products, which leads to increased OS. Similar results were found in patients with vitamin B12 deficiency. Thus, clinical changes in patients with DN may be caused by cellular cobalamin deficiency. In vitro and in vivo studies have demonstrated that vitamin B12 has intrinsic antioxidant activity. Thus, cobalamin, regardless of its classical function as a cofactor, can act as an intracellular, in particular intramitochondrial, antioxidant. This may serve as a rationale for the use of vitamin B12 in the treatment of DN, even in the early subclinical stages. The purpose of this review was to discuss the role of vitamin B12 in the prevention and treatment of DN, as well as to analyze new trends and directions for future research. The search was conducted in Scopus, Science Direct (from Elsevier) and PubMed, including MEDLINE databases. The keywords used were vitamin B12, cobalamin, diabetes mellitus, neuropathy, cardiac autonomic neuropathy. A manual search of the bibliography of publications was used to identify study results that could not be found during the online search.